2015
DOI: 10.1016/j.ijsolstr.2015.04.001
|View full text |Cite
|
Sign up to set email alerts
|

Stress intensify factors for an external circular crack at the interface of a bi-material in shear–compression

Abstract: a b s t r a c tThis paper studies an external circular crack at the interface of a bi-material subjected to shear-compressive loading at the crack surfaces. An axisymmetric problem is solved for an external circular crack where radial shear loadings are applied at the smooth crack surfaces. Across the crack surfaces in contact, there are tangential displacement shift and no normal displacement gap. A mixed boundary value problem is reduced to dual integral equations, and a closed-form solution of the interface… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…Guzina and Pak, 1999;Akarapu and Zbib, 2009). Here we omit the details of derivation (see Li et al, 2015b) and only give final expressions for the interface stresses r zz r; 0…”
Section: Case Of Compressive Forcesmentioning
confidence: 99%
See 1 more Smart Citation
“…Guzina and Pak, 1999;Akarapu and Zbib, 2009). Here we omit the details of derivation (see Li et al, 2015b) and only give final expressions for the interface stresses r zz r; 0…”
Section: Case Of Compressive Forcesmentioning
confidence: 99%
“…Also, Nazarenko et al (2000) analyzed the influence of initial stress on fracture of a half-space containing a penny-shaped crack under shear. Recently, Li et al dealt with an interface crack of two bonded dissimilar elastic half-planes (Li et al, 2015a) and half-spaces (Li et al, 2015b) under shear and compression and found no oscillatory singularity near the crack tips or front.…”
Section: Introductionmentioning
confidence: 99%
“…Physical processes occurring in solids depend significantly on the presence of such defects. An external circular crack in an infinite solid under mechanical loading was investigated in [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 ]. During sudden cooling of a solid, there can arise very high thermal stresses near cracks.…”
Section: Introductionmentioning
confidence: 99%